SIMULASI CFD PROSES PERPINDAHAN PANAS PADA MESIN PENGERING SOHUN KAPASITAS 20 KG DENGAN VARIASI BUKAAN DAMPER - Fauzun, Fauzun; Tamtomo, Danang Eko; Rahman, Muhammad Aulia; Hidayat, Akbar Fadhlurrohman; Yogiswara, Cahyo Wibi (Jurnal Teknologi Terapan, 2025)
Drying machines have a vital role in food products drying for packaging to avoid bacteria contamination and ensure its durability. A properly designed dryer is utterly fundamental to maintaining adequate drying capacity, especially to overcome the ever-changing weather. In aiming for the pre-described drying rate, numbers of parameters need to be considered, such as the drying temperature, airflow speed, temperature distribution, and humidity. Henceforth, a comprehensive study considering all these parameters is necessary during the dryer machine design process. Employing numerical simulation is a solution to reduce the required cost and time from the experimental approach. This study proposed a set of vermicelli dryer designs with various inlet and outlet damper openings of 30%, 45%, and 60%. The study shows that the openings affect the temperature gradient and drying rate. The most optimum design is obtained at the damper opening of 30%, whereby the drying time, temperature gradient, and vermicelli temperature of 23,99 minutes, 2,98 oC and 57,9 oC respectively.